2020
DOI: 10.1590/s1678-9946202062034
|View full text |Cite
|
Sign up to set email alerts
|

Fatal fungaemia due to Cryptococcus albidus in an elderly diabetic woman presenting with pleural effusion

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…noteworthy that most of them are attributed to C. neoformans, with only two reported instances of naganishial pleural effusions. 6,7 Previous case reports indicated that cryptococcal pleural fluid analysis typically exhibits an exudative nature with lymphocyte predominance. 8,9 However, exudative pleural effusion with a lymphocytic predominance can be observed in various diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…noteworthy that most of them are attributed to C. neoformans, with only two reported instances of naganishial pleural effusions. 6,7 Previous case reports indicated that cryptococcal pleural fluid analysis typically exhibits an exudative nature with lymphocyte predominance. 8,9 However, exudative pleural effusion with a lymphocytic predominance can be observed in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐ neoformans cryptococcal infections are increasingly observed in immunocompromised patients with impaired cell‐mediated immunity other than HIV/AIDS, especially organ transplant recipients 4 . Although pleural involvement in cryptococcal infections is a rare occurrence, with approximately only 50 cases documented in a literature, 5 it's noteworthy that most of them are attributed to C. neoformans , with only two reported instances of naganishial pleural effusions 6,7 …”
Section: Discussionmentioning
confidence: 99%
“…N. albidus have a draft genome record in GenBank, which has not yet been updated in the KmerFinder database ( Vajpeyi and Chandran, 2016 ; Yong et al, 2016 ). Many reports showed the clinical importance of these species as opportunistic pathogens ( Ragupathi and Reyna, 2015 ; Aghaei Gharehbolagh et al, 2017 ; Choe et al, 2020 ; Rodriguez-Leguizamon et al, 2020 ); however, none of these less common C. neoformans has been reported from this region before.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the availability and affordability of better-resolution molecular biology techniques, such as DNA sequencing, more reports of infections with previously less reported Cryptococcus species become more evident ( Yong et al, 2016 ; Pakshir et al, 2019 ; Mirpourian et al, 2021 ). Other less common opportunistic Cryptococcus species are becoming an important cause of serious infections such as peritonitis and fungaemia in immunocompromised patients ( Ragupathi and Reyna, 2015 ; Aghaei Gharehbolagh et al, 2017 ; Choe et al, 2020 ; Rodriguez-Leguizamon et al, 2020 ). These infections might not be an emerging infection; however, the availability of whole-genome sequence data and the availability of easy-to-use bioinformatics tools are helping medical microbiology laboratories to better detect and identify these opportunistic Cryptococcus species ( Vajpeyi and Chandran, 2016 ).…”
Section: Introductionmentioning
confidence: 99%